2014
DOI: 10.1186/2049-6958-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response to exercise of elite soccer players

Abstract: BackgroundThe purpose of this study was to evaluate the role of ventilatory parameters in maximal exercise performance in elite soccer players.MethodsFrom September 2009 to December 2012, 90 elite soccer players underwent evaluation of lung function test and ergospirometry by means of an incremental symptom-limited treadmill test. Results were analyzed according to i) maximal exercise velocity performed (Hi-M: high-performers, >18.65 km/h; Lo-M: low-performers, <18.65 km/h) and ii) usual role in the team.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, due to the intensified [13], exhaustive and intermittent [1,3] nature of soccer, other determinants of RE may also provide an indication toward an individual's ability to perform highintensity activities during soccer match-play. Di Paco et al [14] demonstrated an improved ventilatory efficiency for a given exercise intensity in soccer players of a superior fitness level. Consequently, the purpose of this study was to determine the relationship between: VO2max, RE and determinants of RE, and physical measures associated with elite youth soccer performance during soccer match-play within a group of highly trained youth soccer players.…”
Section: Journal Of Physical Fitness Medicine and Treatment In Sportsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, due to the intensified [13], exhaustive and intermittent [1,3] nature of soccer, other determinants of RE may also provide an indication toward an individual's ability to perform highintensity activities during soccer match-play. Di Paco et al [14] demonstrated an improved ventilatory efficiency for a given exercise intensity in soccer players of a superior fitness level. Consequently, the purpose of this study was to determine the relationship between: VO2max, RE and determinants of RE, and physical measures associated with elite youth soccer performance during soccer match-play within a group of highly trained youth soccer players.…”
Section: Journal Of Physical Fitness Medicine and Treatment In Sportsmentioning
confidence: 98%
“…In addition, these same authors reported that other determinants of running economy such as: stride length, stride frequency, respiratory exchange ratio and muscle fibre distribution were unaltered. As a result, the responsiveness of V E to high intensity intermittent training, like that which is experienced during soccer, may have a positive impact on physical performance during soccer matchplay; with players at a higher level demonstrating an enhanced ventilatory efficiency (V E VO 2 ) for a given exercise intensity [14] and therefore increased levels of physical performance during soccer match-play.…”
Section: Journal Of Physical Fitness Medicine and Treatment In Sportsmentioning
confidence: 99%
“…A limitation of conventional face masks is that air may increasingly escape un ltered when ventilation increases from ≈5-10 L/min at rest to over 100 L/min in untrained subjects (30) and up to 200 L/min e.g. in highly trained rowers (31)(32)(33). To address the issue of leakage of un ltered air at high levels of ventilation, a taped face mask was developed, where a " ltering facepiece 2" (FFP2) lter -combined with a laminar KinesioTape -is taped onto the face.…”
Section: Introductionmentioning
confidence: 99%
“…Variables related to breathing pattern and gas exchange were included in the model. Di Paco et al [8] used ventilatory parameters to evaluate professional soccer players' performance. Relation between minute ventilation and oxygen uptake at peak treadmill exercises was constructed for the study.…”
Section: Introductionmentioning
confidence: 99%